GEOCHEMISTRY OF OSTRACODE CALCITE: PART 2. THE EFFECTS OF WATER CHEMISTRY AND SEASONAL TEMPERATURE VARIATION ON CANDONA RAWSONI - Xia J.; Engstrom D.R.; Ito E. (My University, 1997)
Reconstruction of lake paleochemistry from the isotope and trace-element composition of fossil ostracodes requires an understanding of geochemical variations induced by the seasonality of shell formation. Monthly field collections of live Candona rawsoni from two hyposaline lakes in the eastern Dakotas reveal large variations in δ18O values (2-5%%) and Mg/Ca and Sr/Ca ratios (up to 35%) among individual adults within the same assemblage. Because the measured variations in water chemistry were small, the amplitude of ostracode δ18O and Mg/Ca variations must result from seasonal temperature variation. Ostracode Sr/Ca ratios, which should be temperature independent, shows strong positive covariance with shell Mg/Ca. These results imply that Sr uptake in ostracode calcite increases with the Mg content of the shell. The partitioning coefficient for Mg, on the other hand, appears to decreases at high values of Mg/Ca in the host water.The geochemical variability in the field collections indicates that C. rawsoni populations are composed of multiple overlapping generations that attain maturity at different times. Many juveniles apparently undergo several molts in mid-summer and persist as penultimate instars (A-1) into the following spring. Geochemical analysis of late-instar juvenile C. rawsoni from lacustrine sedimentary records is likely to provide information on mid-summer conditions. Large numbers of fossil ostracodes should be analyzed from each stratigraphic interval to eliminate seasonal noise from the paleochemistry records of temperate-region lakes.